Targets for endothelin in the diseased kidney: clues for therapeutic intervention - Rohmeiss, Peter; Birck, Rainer; Braun, Claude; Kirchengast, Michael; Woude, Fokko J. van der (Nephron, 1999)
The endothelin system has been implicated in various renal diseases. This review focuses on the involvement of endothelin-1 in pathogenesis and pathophysiology of acute and chronic renal failure with regard to its hemodynamic and nonhemodynamic effects. Future developments concerning the use of endothelin receptor antagonists and the role of endothelin in the kidney transplantation setting are discussed.